Pengenalan & Pelatihan “Fast Math Tricks” Bagi Siswa Sekolah Dasar Jemaat GMIT Petra Kefamenanu - Justin Eduardo Simarmata; Merlin Helentina Napitupulu; Thresia Trivict Semiun; Maria Wisrance Wihelmina (ABDIMASKU : JURNAL PENGABDIAN MASYARAKAT, 2021)
Introduction and training of “Fast Math Tricks” for elementary school students in GMIT Petra Kefamenanu congregation aims to develop students' thinking skills and interest in mathematics. This community service activity is carried out for one month, with a meeting duration of 90 minutes per meeting. Students who take part in the activity are students who are considered capable of participating in the training, come from the sixth grade of elementary schools in the GMIT Petra Kefamenanu congregation. The method of implementing this activity is the method of testing, lecturing, and practice. The activity began with an introduction to "Fast Math Tricks", followed by training on "Fast Math Tricks". With the introduction and training of "Fast Math Tricks", students understand and like mathematics more and will become provisions for students for education at the next level. Student response is very good in implementing activities because "Fast Math Tricks" is a new thing for them, in addition to the introduction of "Fast Math Tricks", it can provide benefits and convenience for elementary school students in doing calculations. From the introduction and training activities of fast math tricks, it was concluded that students were 87.50% helped, 8.33% was quite helpful, and 4.17% were not helped by the application of fast math tricks in calculating multiplication and division.